2020
DOI: 10.4047/jap.2020.12.6.344
|View full text |Cite
|
Sign up to set email alerts
|

How adjustment could affect internal and marginal adaptation of CAD/CAM crowns made with different materials

Abstract: PURPOSE.Recently introduced hybrid and reinforced glass ceramic computer-aided design/computer-aided manufacturing (CAD/CAM) materials have been used for full-coverage restorations. However; the effect of adjustment and type of materials on internal and marginal adaptation are unknown. This study aimed to evaluate and compare the marginal and internal adaptations of crowns made of three different CAD/CAM materials before and after adjustment. MATERIALS AND METHODS. One acrylic resin maxillary first molar was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…Although statistically significant differences were found in MG between the PICN (36 µm) and LDS (57 µm) crowns in this investigation, the magnitude of the disparity was small and the clinical significance of such a difference is unknown. The mean AMD values were markedly higher than the MG values in this paper for both the materials, in line with the findings of previous studies [7,9,15].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Although statistically significant differences were found in MG between the PICN (36 µm) and LDS (57 µm) crowns in this investigation, the magnitude of the disparity was small and the clinical significance of such a difference is unknown. The mean AMD values were markedly higher than the MG values in this paper for both the materials, in line with the findings of previous studies [7,9,15].…”
Section: Discussionsupporting
confidence: 93%
“…The mean ± sd MG values obtained in this study for PICN crowns (36 ± 24 µm) were close to the numbers (51 ± 15 µm) reported in a recent PICN crown fit study [9], and also matched the lower side of the MG range (38-81 µm) seen in another similar study [8]. With regard to the AMD, two studies found values of 147 µm [9] and 183-212 µm [7] with PICN crowns, much higher than the current mean AMD value of 109 µm. So, generally, the marginal discrepancies in this study were found to be lower than those reported for PICN crowns in the literature for both MG and AMD parameters.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations